Design and Explanation of an IoT Utilization Model in Export Businesses: Identifying Antecedents and Consequences - Hosseini , Seyyed Ali; Omidi , Fereydoun; Rekabdar , Ghasem (Business, Marketing, and Finance Open, 2024)
Technologies have significantly influenced business practices, and it can be stated that businesses that do not align with this revolution have little chance of survival. Accordingly, the present study aims to identify the antecedents and consequences of the utilization of the Internet of Things (IoT) in export businesses dealing with agricultural products. This study is applied in terms of purpose, developmental in nature, and employs a mixed-methods approach. The qualitative sample consists of experts and managers from agricultural machinery exporting companies. A total of 13 participants were selected using purposive snowball sampling, and semi-structured interviews were conducted with them. Data analysis in the qualitative phase was performed using thematic analysis based on the three-stage coding method proposed by Braun and Clarke (2006). The quantitative sample, considering an unlimited population, was determined based on Morgan’s table and included 384 managers, supervisors, and specialists from exporting companies, selected through convenience random sampling. Data in the quantitative section were collected using a researcher-developed questionnaire, the validity and reliability of which were confirmed. Furthermore, data analysis in the quantitative phase was conducted using structural equation modeling (SEM) with SmartPLS software. The results of the qualitative phase revealed that the most critical antecedents of IoT utilization in export businesses include market and customer needs, decision-making and planning, goal setting, technical infrastructure, and the company environment. Additionally, the consequences of IoT utilization in export businesses encompass market alignment, performance improvement, and profitability. Finally, in the quantitative phase, the relationships between variables were examined through structural equations, and the results indicated significant relationships among the variables. This finding confirmed the proposed IoT utilization model in export businesses.